Geotechnical studies of the Lam Ta Khong pumped storage project, Thailand - Dhakal, Ganesh P.; Onodera, Kazumoto; Yoneda, Tetsuro (Journal of Nepal Geological Society, 2000)
The Lam Ta Khong Project in Nakhornratchasima is the biggest pumped storage hydropower project of Thailand. The project is capable of producing 1,000 MW of electricity at the peak hour of demand. It consists of an upper pond transitory reservoir, twin inclined penstocks, a powerhouse, twin surge chambers, and twin tailrace tunnels. The powerhouse is underground with the dimensions of 175x25x50 m3, and houses 4 (each of 250 MW capacity) Francis type reversible pump turbines. The rock mass classification system of the Electric Power Development Co. Ltd. (EPDC), Japan, was used in the project area in order to select an appropriate support system for the tunnel. The majority of rocks in the project area are sandstone and siltstone. The sandstone is interbedded with claystone at shallow depths. The sandstone at greater depths is fine grained and contains two sets of joint nearly perpendicular to each other and almost vertical. These joints were responsible for frequent block falls during the excavation. Especially, the joint surfaces with slickensides contributed to frequent block falls. The near-surface highly weathered rocks required stronger support for the excavated part than the less weathered ones at greater depths. The deformation of rock mass due to excavation in the powerhouse was monitored by nine multiple borehole extensometers with one to four measuring heads (points). The monitoring results showed safe conditions in the powerhouse.